Mitochondrial autophagy-related lncRNAs as prognostic biomarkers and therapeutic targets in gastric adenocarcinoma - Rongbo Han; Jinxin Wei; Benxin Zhao; Rongchang Zhao (Discover Oncology)
Abstract Understanding the tumor microenvironment (TME) and the role of long noncoding RNAs (lncRNAs) in gastric adenocarcinoma (GA) is crucial, as these elements not only influence tumor progression but also provide opportunities for more precise prognostic assessments and tailored therapeutic interventions. This study identified mitochondrial autophagy-related lncRNAs, constructed a robust prognostic risk model, and explored the relationship between immune microenvironment characteristics and therapeutic responses. The model’s performance was evaluated using ROC curves, Kaplan–Meier survival analysis, and nomograms. Our results demonstrate that the model outperforms traditional clinical factors, such as age and stage, in predicting patient outcomes. Immune cell analysis revealed distinct correlations with risk scores, and several immune checkpoint genes exhibited differential expression between risk groups. Drug sensitivity analysis suggested that low-risk patients could benefit more from ICIs, Oxaliplatin, Irinotecan, Afatinib, and Dabrafenib, while high-risk patients showed higher sensitivity to IGF1R3801, JQI, WZ4003 and NU7441. The identified lncRNA-based risk model provides a reliable prognostic tool for GA patients and highlights distinct immune microenvironment profiles that may influence treatment responses. These findings contribute to developing personalized therapeutic strategies targeting lncRNAs and the TME in GA.